Nutrition and Breastfeeding in the View of Islam to Prevent Acute Respiratory Infections in Toddlers - Irma, Irma; Kamrin, Kamrin; Harleli, Harleli; Handayani, Arini (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2023)
Acute Respiratory Infection (ARI) in Indonesia generally occurs in urban areas and always ranks first as a cause of death in infants or toddlers. Studies on the incidence of ISPA in toddlers in rural areas are still rarely studied. This study aims to analyze the relationship between nutritional status and exclusive breastfeeding with the incidence of ARI in toddlers. This study was an analytic survey study with a case-control design. The population in this study consisted of 68 toddlers diagnosed with ISPA and all of them were sampled with a ratio of 1:1 and the total sample was 136 people. The toddler's mother pleaded as the respondent. The instruments used were questionnaires and health cards (KMS) for toddlers. Data analysis used is chi square. Statistical analysis of the relationship between nutritional status and the incidence of ARI (P=0.001) and the relationship between exclusive breastfeeding and ARI was obtained (P=0.001). This means that there is a significant relationship between nutritional status and exclusive breastfeeding program and the incidence of ARI. Nutritional status and exclusive breastfeeding programs contribute to the incidence of ARI among toddlers in rural areas. This study recommends that mothers prioritize giving primary food to babies in the form of exclusive breastfeeding for 2 years according to the guidance of the Koran. This action will greatly affect the nutritional status of toddlers, especially in preventing ARI.